Changing Home: Experiences of the Indigenous when Receiving Care in Hospital - Juan Guillermo Rojas; Raquel Herrero Hahn (Universidad de Antioquia, 2020)
Objective. To understand the meaning of the experience of the indigenous when receiving care in a low-complexity hospital. Methods. Qualitative study with ethnographic approach conducted in a hospital of Antioquia, Colombia. The study had 12 indigenous participants who underwent semi-structured interviews. Observation was carried out in hospitalization wards, emergency, and outpatient services of the institution during 40 hours. The analysis process was performed descriptively. The methodological rigor was maintained by applying criteria of confirmability, credibility, transferability, and consistency. The study was approved by the Ethics Committee and authorized by the indigenous authorities to enter the field. Results. Five themes emerged: the context of caring for the indigenous, the need to consult the hospital, changes experienced by the indigenous in the hospital, experiences in relation with treatments, and relations established within the hospital. The meaning is constructed from a dichotomous perspective based on the favorable or unfavorable aspects of the situations and experiences, which for the indigenous is like "changing home". Conclusion. The meaning of the experience of receiving care in hospital for the indigenous is constructed from the context in which they live and receive health services, the changes they live in the dimension of space by virtue of their traveling from their vital space to another space that, due to their physical characteristics, results strange and different, even not healing. Upon the difficulties, the indigenous develop strategies and actions to overcome limitations, whether through adaptation and learning.